Characterization of a Flavobacterium glutathione S-transferase gene involved reductive dechlorination. - Orser, C S (1993)
The gene pcpC, encoding tetrachloro-p-hydroquinone (TeCH) reductive dehalogenase, was cloned from Flavobacterium sp. strain ATCC 39723 and sequenced. The gene was identified by hybridization with a degenerate oligonucleotide designed from the N-terminal sequence of the purified protein. An open reading frame of 747 nucleotides was found, which predicts a translational product of 248 amino acids having a molecular weight of 28,263, which agrees favorably with the sodium dodecyl sulfate-polyacrylamide gel electrophoresis-determined molecular weight of 30,000 reported for the purified protein. The predicted translational product of pcpC matched the N-terminal sequence of the purified protein exactly. From the nucleotide sequence, the protein appears to have a processed formylmethionyl. An Escherichia coli pcpC overexpression clone was shown to produce dichlorohydroquinone and trichlorohydroquinone from TeCH. Protein data base searches grouped the predicted translational sequence of pcpC with two previously reported plant glutathione S-transferases but less significantly with any of the mammalian glutathione S-transferases or the glutathione-utilizing, hydrolytic dechlorinating enzyme from Methylobacterium sp. strain DM4.